Influence The Application Of The Paragraph Building Method In Arabic Language Learning To Increase The Writing Skill At Madrasah Aliyah Darul Faizin Catak Gayam Mojowarno Jombang - Abidin, Hasan (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2021)
This journal explains about